Evaluation of Haematological Ratios at: Different Stages of Canine Periodontal Disease - Carolina Silva; Ana Carolina Abrantes; Ana Carolina Fontes; Isabel Dias; Rosário Domingues; Francisco Peixoto; Carlos Viegas (Veterinary Sciences)
This is a retrospective study about haematological ratios in different stages of canine periodontal disease in one single breed, more specifically the Portuguese Podengo. The aim of the study was to assess the clinical significance of five haematological ratios, namely neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), mean platelet volume-to-platelet count ratio (MPV/PLT), monocyte-to-lymphocyte ratio (MLR), and platelet-to-neutrophil ratio (PNR), easily obtained through the parameters provided by the complete blood count, in the stages of gingivitis and periodontitis, compared to clinical healthy individuals. Receiver operating characteristic curves were generated to identify ideal sensitivity and specificity cut-offs for cases of gingivitis or periodontitis. Our study included 80 dogs, which comprised 24 healthy dogs, 26 diagnosed with gingivitis, and 30 with periodontitis. The median NLR was significantly lower in periodontitis than in clinical healthy dogs (p = 0.040) and in dogs with gingivitis (p = 0.037). The median PLR was significantly lower in cases of gingivitis (p = 0.020) and periodontitis (p = 0.024) than in healthy dogs. MPV/PLT and MLR did not demonstrate significant differences between any of the three groups. The median PNR was significantly lower in gingivitis than in control dogs (p = 0.019). PNR had the highest accurate results, in distinguishing between healthy individuals and those with gingivitis, with an area under the curve of 0.692 (95% CI [0.539–0.845], p = 0.020). However, even this index had weak discriminatory power between the groups in the analysis. The impact of systemic inflammation generated by canine periodontal disease can thus be seen through some of these indices. However, the results obtained here demonstrate the need for complementarity with other methods to diagnose canine periodontal disease and reinforce the need for additional studies with more markers of systemic inflammatory response.